TIL VA HURMAT: O‘ZBEK VA INGLIZ TILLARIDAGI HURMAT IFODALARI (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This research paper analyzes the specific features of politeness in Uzbek and English. The article examines the influence of grammatical and lexical means used to express politeness in both languages, as well as cultural factors. In the Uzbek language, politeness is often based on the rules of perfect literature and the formal structure of the text, while in English, direct and informal methods are more often used.